Gnathiidae from Kumejima Island in the Ryukyu Archipelago, southwestern Japan, with description of three new species (Crustacea: Isopoda) - Ota, Yuzo (Zootaxa, 2012)
A marine biodiversity expedition was carried out from 7 November to 22 November 2009 in Kumejima Island, the RyukyuArchipelago, southwestern Japan. The dredge and trawl samplings from 10 to 147 m depths yielded five gnathiid speciesincluding three new Gnathia species. In this paper, these three new species are described based on male morphologies and three morphotypes of larvae are also described.